Perinatal outcomes of twin pregnancies complicated with preeclampsia at a tertiary hospital in Ethiopia: A case‐control study - Abraham Fessehaye Sium; Don Eliseo III Lucero‐Prisno; Wondimu Gudu (Wiley, 2022)
Abstract Background Preeclampsia accounts for 10-15% maternal deaths globally, corresponding to 50,000 annual maternal deaths. Twin pregnancy is a known risk factor for preeclampsia; however, there is inadequate data on the clinical characteristics and perinatal outcomes of twin pregnancies complicated with preeclampsia. This paper studied the perinatal outcomes of twin pregnancies complicated with preeclampsia at a tertiary hospital in Ethiopia. Methods A case‐control study was conducted at St. Paul's Hospital Millennium Medical College (Addis Ababa, Ethiopia) from September 1, 2016 till August 31, 2018. A total of 173 twin deliveries (63 preeclampsia cases and 110 normotensive controls) were included in the study and the primary outcome was the frequency of preterm delivery. Data were analyzed using SPSS version 23 and statistical test of association was done using chi‐square test for categorical data. Variables with p value of <0.2 on bivariate analysis were entered into multivariable logistic regression analysis. p value <0.05 were considered significant. Results The frequency of preterm birth was 61.9% in the preeclampsia group and 33.6% in the normotensive group, p < 0.001. Preeclampsia group were 2.58 times more likely to have preterm delivery compared to matched normotensive controls [adjusted OR = 2.58, 95% CI (1.24 - 5.35), p = 0.01]. There was no difference in the rate of adverse neonatal outcome (respiratory distress syndrome, early neonatal death, and Low Apgar score) between the groups. Conclusions In this study, twin pregnancies complicated with preeclampsia were found to have an increased rate of preterm birth compared to matched controls without hypertension.